The book unbound : editing and reading medieval manuscripts and texts - Echard, Siân, 1961-; Partridge, Stephen (Studies in book and print culture., 2004)
"In The Book Unbound scholars and editors examine how best to use new technological tools and new methodologies with artefacts of medieval literature and culture. Taking into consideration English, French, Anglo-Norman, and Latin texts from several periods, the contributors examine and re-evaluate traditional approaches to and conclusions about medieval books and the cultural texts they contain - literary, aromatic, legal, historical, and musical. The essays range from detailed examinations of specific codices to broader theoretical discussions on past and present editorial practices."--Jacket.